The Effect of the POE Learning Model on Students' Cognitive Learning Outcome - Noviyanti, Mila Anggita; Rettob, Abraham Laurens; Parlindungan, John Yoro; Siregar, Lamtiar Ferawaty; Sumanik, Novike Bela; Asmaningrum, Henie Poerwandar (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2025)
This study investigates the effectiveness of the POE learning model in enhancing cognitive learning outcomes of chemistry education students, with particular emphasis on redox reaction concepts in the Basic Chemistry 2 course. The research is motivated by the persistent challenge that chemistry is perceived as abstract and calculation-intensive, which hinders students’ conceptual understanding and reduces academic achievement. Employing a pre-experimental one-group pre-test – post-test design, data were collected from 12 second-semester students at Musamus University. Validated essay-based instruments were used to measure learning outcomes, and data analysis included N-Gain testing, Shapiro–Wilk normality testing, and paired sample t-tests. Results revealed a significant improvement in students’ performance, with mean scores rising from 19.4 (pre-test) to 74.6 (post-test), an N-Gain score of 0.67 categorized as moderate, and a t-count of 9.360 exceeding the t-table value of 2.22. The novelty of this research lies in the contextual application of the POE model under pandemic-induced learning constraints, demonstrating that active learning strategies integrating prediction, observation, and explanation are effective even within limited instructional settings. The contribution of this study is twofold: theoretically, it reinforces constructivist approaches in chemistry education by providing empirical evidence of POE’s impact on cognitive outcomes; practically, it offers lecturers a viable pedagogical alternative to foster motivation, engagement, and deeper understanding of abstract chemical concepts. These findings underscore the potential of POE as a scalable instructional strategy to address learning challenges in higher education science contexts.